Bioactive Plasma Mitochondrial DNA Is Associated With Disease Progression in Scleroderma‐Associated Interstitial Lung Disease. Issue 11 (8th October 2020) - Ryu, Changwan; Walia, Anjali; Ortiz, Vivian; Perry, Carrighan; Woo, Sam; Reeves, Benjamin C.; Sun, Huanxing; Winkler, Julia; Kanyo, Jean E.; Wang, Weiwei; Vukmirovic, Milica; Ristic, Nicholas; et al.
Abstract : Objective: Systemic sclerosis–associated interstitial lung disease (SSc‐ILD) is characterized by variable clinical outcomes, activation of innate immune pattern‐recognition receptors (PRRs), and accumulation of α‐smooth muscle actin (α‐SMA)–expressing myofibroblasts. The aim of this study was to identify an association between these entities and mitochondrial DNA (mtDNA), an endogenous ligand for the intracellular DNA–sensing PRRs Toll‐like receptor 9 (TLR‐9) and cyclic GMP‐AMP synthase/stimulator of interferon genes (cGAS/STING), which has yet to be determined. Methods: Human lung fibroblasts (HLFs) from normal donors and SSc‐ILD explants were treated with synthetic CpG DNA and assayed for α‐SMA expression and extracellular mtDNA using quantitative polymerase chain reaction for the human MT‐ATP6 gene. Plasma MT‐ATP6 concentrations were evaluated in 2 independent SSc‐ILD cohorts and demographically matched controls. The ability of SSc‐ILD and control plasma to induce TLR‐9 and cGAS/STING activation was evaluated with commercially available HEK 293 reporter cells. Plasma concentrations of type I interferons (IFNs), interleukin‐6 (IL‐6), and oxidized DNA were measured using electrochemiluminescence and enzyme‐linked immunosorbent assay–based methods. Extracellular vesicles (EVs) precipitated from plasma were evaluated for MT‐ATP6 concentrations and proteomics via liquid chromatography mass spectrometry. Results: Normal HLFs and SSc‐ILD fibroblasts developed increased α‐SMA expression and MT‐ATP6 release following CpG stimulation. Plasma mtDNA concentrations were increased in the 2 SSc‐ILD cohorts, reflective of ventilatory decline, and were positively associated with both TLR‐9 and cGAS/STING activation as well as type I IFN and IL‐6 expression. Plasma mtDNA was not oxidized and was conveyed by EVs displaying a proteomics profile consistent with a multicellular origin. Conclusion: These findings demonstrate a previously unrecognized connection between EV‐encapsulated mtDNA, clinical outcomes, and intracellular DNA–sensing PRR activation in SSc‐ILD. Further study of these interactions could catalyze novel mechanistic and therapeutic insights into SSc‐ILD and related disorders.